Pengaruh Kebijakan Dividen Dan Hutang Terhadap Nilai Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2021-2024: The Effect of Dividend and Debt Policies on the Value of Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange Period 2021-2024 - Siti Harum Sari Nadiyanti; Eulin Karlina (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The purpose of this research is to examine the relationship between company value and dividend and debt policies for food and beverage firms traded on the IDX in Indonesia from 2021 to 2024. The Price to Book Value (PBV) indicator is used to assess firm value, while the Dividend Payout Ratio (DPR) and the Debt to Equity Ratio (DER) are used to measure dividend policy and debt policy, respectively. The study approach used is SPSS-processed quantitative statistics. Information is collected from the yearly financial reports that the sampled corporations have made public. A purposive selection technique, based on predetermined criteria, was used to choose the study sample. Firm value was shown to be significantly affected by both debt policy and dividend policy at the same time. Investors should pay attention to dividend policy and corporate debt policy as signals for evaluating firm value, according to signal theory and capital structure theory. This finding backs up these claims. Findings from this research suggest that, in this industry specifically, investors' views of company value may be more heavily impacted by variables other than financial policy